Efektifitas Madu Sebagai Substituen Media Induksi Kalus Sorgum (Sorghum bicolor) Secara In Vitro - Laras Sekar Arum; Levinia Wuri Safitri; Hidayah Murtiyaningsih; Muhammad Hazmi (Paspalum: Jurnal Ilmiah Pertanian, 2022)
Sorghum is one of the five most important cereal crops  in the world, due to its multi-beneficial usages and wide adaptability, so it has the high potential to be developed. One of the current efforts to develop sorghum is through a modern technique, molecular-based. Thus, in vitro culture is an indispensable basic technique, especially in the callus formation process. In addition to commercial synthetic chemicals, various organic materials found in nature have the potential to be used as PGR in initiating callus formation, one of which is honey. This study aims to obtain the optimum concentration of honey as a substituent of sorghum callus induction medium. The research design used a completely randomized design with one factor (honey concentration), which consisted of 5 dffrent levels (0, 5, 15, 25 and 35 gL-1). Observation variables consisted of callus formed (hsi), percentage of callus formation (%) and callus morphology. Data were analyzed using the F variance test and DMRT test at the 5% level. The test results of this study indicate that the two variables are significantly different. The fastest callus formation was in the M0 medium (0 gL-1.), while in the percentage of callus formation. The best results were in the M4 honey treatment (35 gL-1) of 77.78%. Thus it can be seen that the administration of honey as a substituent of in vitro culture media can help increase the success of sorghum callus formation.